Analysis of completeness factors for filling inpatient discharge summaries H. Hanafie regional hospital Muara Bungo Jambi 2024 - Astrianda, Veita; Sukmaningsih, Wahyu Ratri (Institute of Computer Science (IOCS), 2025)
Although the discharge summary is essential for ensuring continuity of patient care, supporting clinical decision-making, and enabling administrative processes such as BPJS insurance claims, RSUD H. Hanafie Muara Bungo continues to face challenges in achieving complete and standardized medical documentation. This study analyzes the factors influencing the completeness of inpatient medical resumes at RSUD H. Hanafie using the 5M framework: Man, Method, Machine, Material, and Money. A qualitative descriptive approach was employed, with data collected through document review, observation, and interviews with Responsible Doctors (DPJP) and the Head of the Medical Records Installation. A total of 100 medical resumes were selected using simple random sampling, based on the Slovin formula with a 10% margin of error. Data were analyzed through data reduction, presentation, conclusion drawing, and validation using triangulation. Results showed that the patient identification component achieved 100% completeness, while important reporting, authentication, and recording reached 98%, 95%, and 77%, respectively. Key influencing factors included limited routine training and discipline (Man), absence of SOPs and weak monitoring (Method), suboptimal form design (Material), insufficient devices and system disruptions (Machine), and budget constraints (Money). To address these issues, a comprehensive strategy involving health worker collaboration, system support, and strong management commitment is essential to ensure that the clinical, legal, and administrative functions of medical resumes are fulfilled.